2017
DOI: 10.1590/1809-4430-eng.agric.v37n2p246-256/2017
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Nutritive Value of Tifton 85 in Summer, With and Without Irrigation Under Different Nitrogen Doses

Abstract: ABSTRACT:The pasture irrigation has expanded, mostly in small areas in order to boost the production system, along with the use of soil improvement techniques and high-productivity grasses. Thus, this study, carried out on a small dairy farm property, aimed to evaluate the productivity, botanical composition and nutritive value of Tifton 85 with different nitrogen (N) doses, in the presence and absence of irrigation. The experimental design was a randomized block in a split-plot design with four replications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 22 publications
2
17
0
16
Order By: Relevance
“…The presence of nitrogen positively influenced the TFP and LSP in the cycles (Fig 5.c, (Quaresma et al, 2011;Gomes et al, 2015b;Taffarel et al, 2016;Sanches et al, 2017). Sanches et al (2017) and Quaresma et al (2011) In relation to the SW doses applied in Tifton 85 grass ( Fig 4A), other authors have also observed the occurrence of increasing linear behaviour in dry matter yield.…”
Section: Yield Parameters Of Forage Dry Mattermentioning
confidence: 74%
See 3 more Smart Citations
“…The presence of nitrogen positively influenced the TFP and LSP in the cycles (Fig 5.c, (Quaresma et al, 2011;Gomes et al, 2015b;Taffarel et al, 2016;Sanches et al, 2017). Sanches et al (2017) and Quaresma et al (2011) In relation to the SW doses applied in Tifton 85 grass ( Fig 4A), other authors have also observed the occurrence of increasing linear behaviour in dry matter yield.…”
Section: Yield Parameters Of Forage Dry Mattermentioning
confidence: 74%
“…However, this supplemental irrigation could no eliminate the seasonality (Sanches et al, 2015). In this sense, we highlight the Cynodons, which has presented excellent productive results with irrigation, attenuating the seasonality with good nutritional results, especially the Tifton 85 grass (Gomes et al, 2015b;Sanches et al, 2015Sanches et al, , 2016Sanches et al, , 2017.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Studies have shown that irrigated grasslands may have higher and more stable rates of yield [6][7][8]. However, achieving high output yields with less irrigation in an efficient and sustainable manner is one of the key challenges in artificial grasslands in arid areas.…”
Section: Introductionmentioning
confidence: 99%